Maps - Howell, Izzi; Evans, Steve (Chicago : World Book, a Scott Fetzer Company, 2023)
A graphic nonfiction volume that describes the different types of maps, how they are made, and how to read them.
What is a map? -- Types of maps -- Map scales -- Map symbols and legends -- Map compass -- Topographic maps -- Grid reference system -- Latitude and longitude -- Maps and globes -- How maps are made -- Maps today -- Can you believe it?! -- Words to know.
Include glossary
Primary
Keywords: Maps -- Juvenile literature; Maps -- Comic books, strips, etc; Maps -- Symbols -- Juvenile literature; Maps -- Symbols -- Comic books, strips, etc; Map reading -- Juvenile literature; Map reading -- Comic books, strips, etc; Cartography -- Juvenile literature; Cartography -- Comic books, strips, etc; Geography -- Juvenile literature; Geography -- Comic books, strips, etc